Mechanical behaviour of rapidly solidified copper: effects of undercooling and strain rate. Issue 2 (22nd January 2020) - Dragnevski, Kalin I.; Pellegrino, Antonio; Heard, Rhiannon; Siviour, Clive R.; Mullis, Andrew M.; Cochrane, Robert F.
Abstract : In this paper we present the results, from what we believe is the first ever attempt to study the mechanical behaviour of pure highly undercooled Cu specimens. The data revealed that the strength of the studied system increases not only with an increase of the level of undercooling, but also with the rate of testing. Microstructural analysis demonstrated that at undercoolings above 200 K the specimens underwent a transition from dendritic to a grain refined structure, accompanied with a break in the stress-undercooling relationship. It is suggested that on this occasion the transition was the result of two competing mechanisms: dendrite fragmentation and recrystallization. Finally, the relationship between the resultant grain sizes and measured stresses is compared against the Hall-Petch Law.